The effects of land use change, from small livestock farming to protected area, on vegetation and mammal communities in the SKA region of the Karoo, South Africa - Blanckenberg, Michelle Claire (Department of Biological Sciences, 2022)
Land-use change, particularly agriculture, has been identified as one of the major drivers of biodiversity loss worldwide. Meeting global biodiversity targets requires both the establishment of protected areas (PAs) and learning to coexist with wildlife in human-modified landscapes, particularly extensive rangelands. In the semi-arid regions of the Karoo, South Africa, small livestock production has been the primary land use for more than 350 years. This extensive agricultural activity has allowed much of the native flora and fauna to persist leading to a complex interplay between vegetation, livestock, humans and wildlife. Most farmers strive to optimise livestock production and thus actively seek to reduce or eradicate wild predators and competitors of livestock. It is against this background that the recent establishment of a large (131 000 ha) protected area within a well-established small livestock farming region in the Karoo represents a rather unprecedented event with clear benefits for biodiversity and both real and perceived costs to the farming community. This landscape level shift in land use from farming to protected area provided a unique opportunity to design a Before-After-ControlIntervention (BACI) study investigating how a cessation in farming activity impacts both natural vegetation and wildlife. I hypothesised that this change would positively impact vegetation, and small and medium/large mammals. To test this, I compared biota using standard surveys on farms before and after the cessation of farming (core, n = 3) and compared this to both neighbouring farms (edge, n = 3) that are likely to be impacted by the land use change and farms at least 50 km from the new PA (control, n = 3). I also explored the condition, maintenance levels and success of fences between the core and edge farms at preventing the movement of wildlife onto edge farms. Before the cessation of farming activities on the core, species richness and the abundance of vegetation, small mammals and medium/large mammals were similar across all farm types. After the cessation of farming activities forb cover and grass height increased slightly on core farms, while small and medium/large mammal richness and abundance remained constant. Daily activity patterns for several medium sized mammals shifted on the core farms from almost exclusively nocturnal to more diurnal. Both caracal and black-backed jackal naïve occupancy remained constant on all farm types over the study period. Despite this, edge farmers (as well as control farmers) complained of increased predator numbers and livestock losses and their attitudes to predators and the PA worsened over the study period. These perceived changes may well have been attributed to the extreme drought conditions that prevailed during the study. Most farmers resorted to food provisioning which concentrates livestock at feeding sites and around farm buildings both increasing the detection of livestock by predators and the detection of predators by farmers. Well maintained fences significantly reduced wildlife movement in general and predator movement from the core to edge farms. Poor quality and poorly maintained fences had a higher incidence of mammal movement along the fence line and a higher frequency of hole utilisation, particularly by small and medium sized herbivores. Overall, my results support expert predictions that the recovery of both flora and fauna in the Karoo following cessation of sustained livestock farming will be slow and dependent on rainfall. The drought conditions that prevailed during the study may well have dampened a resurgence in primary productivity on core farms and with that the recovery of small mammals and medium sized herbivores, followed by their predators. It will be important to continue monitoring these farms over the medium/long term to better understand the relative impacts of farmers and livestock on the flora and fauna of the Karoo and the recovery of biota within this newly proclaimed PA especially where abiotic factors such as variability of rainfall may confound these influences. In the interim improving relationships between farmers and managers of the PA is essential and will largely depend on the quality and maintenance of the fence line that separates these different land uses.